2013
DOI: 10.1371/journal.pone.0064170
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin: An Excitatory Modulator of Mitral/Tufted Cells in the Mouse Olfactory Bulb

Abstract: Cholecystokinin (CCK) is widely distributed in the brain as a sulfated octapeptide (CCK-8S). In the olfactory bulb, CCK-8S is concentrated in two laminae: an infraglomerular band in the external plexiform layer, and an inframitral band in the internal plexiform layer (IPL), corresponding to somata and terminals of superficial tufted cells with intrabulbar projections linking duplicate glomerular maps of olfactory receptors. The physiological role of CCK in this circuit is unknown. We made patch clamp recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…For example, negative coupling between neural activity during spike bursts and glutamate uptake by astroglial transporters has been reported (Armbruster et al, 2016). Another scenario that we cannot completely exclude is one in which repetitive spiking in eTCs recruits the release of excitatory neurotransmitters other than glutamate (Ma et al, 2013). In our experiments, we found that blockade of ionotropic glutamate receptors reduced most (∼70%) of even the largest EC extra responses ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, negative coupling between neural activity during spike bursts and glutamate uptake by astroglial transporters has been reported (Armbruster et al, 2016). Another scenario that we cannot completely exclude is one in which repetitive spiking in eTCs recruits the release of excitatory neurotransmitters other than glutamate (Ma et al, 2013). In our experiments, we found that blockade of ionotropic glutamate receptors reduced most (∼70%) of even the largest EC extra responses ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this prediction contradicted a recent report that CCK at 1 μ m excited majority of MTCs (Ma et al . ). Considering that cesium and QX‐314 in the voltage clamp pipette solution non‐selectively block K + , Na + and other ion channels (Perkins & Wong, ; Talbot & Sayer, ), we then examined the effects of CCK on the intrinsic electrophysiological properties of a separate sets of MTCs with intact apical dendrites in current clamp with K + ‐based intracellular solution containing no QX‐314 in the presence of NBQX, APV and GBZ to eliminate circuit influence.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, a recent study showed that CCK mainly excited MTCs (Ma et al . ). However, at least two pieces of evidence support the idea that the CCK‐enhanced synaptic inhibition of MTCs is not a result of feedback inhibitory input following direct excitation of MTCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This bottom-up processing of afferent signals is controlled by modulatory top-down signals, which reach the olfactory bulb from various cortical areas and other brain regions through centrifugal innervation (Matsutani & Yamamoto, 2008;Mouret et al, 2009;Boyd et al, 2012;Nunez-Parra et al, 2013). Cholinergic, serotonergic and adrenergic neuromodulation of bulb circuits have recently been examined in detail (Li & Cleland, 2013;Devore et al, 2014;Eckmeier & Shea, 2014;Rothermel et al, 2014;Schmidt & Strowbridge, 2014;Liu et al, 2015;Parsa et al, 2015;Smith et al, 2015;Brill et al, 2016;Kapoor et al, 2016), and other systems contribute as well (Tobin et al, 2010;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%